Miopía alta y queratocono en paciente pediátrico de 10 años de edad. - Castro Ochoa, Rosa Angelica (2022)
When high myopia in a pediatric patient (children) and a keratoconus develops along whit it, it is inexcusable to subordinate its development, aiming to delay its evolution and an irreversible impact such as vison loss. Knowing that the vision or the eyes “are the window of the soul” the care of them must be as delicate and demanding as possible. The case study presented is used in a 10-year-old pediatric patient who manifests eminent myopia, he attends consultation manifesting difficulty in focusing, migraine and eye fatigue, resulting in keratoconus. After using the relevant tests, treatment with scleral design contact lenses is determined. Scleral contact lenses are recommended in cases where patients have corneal irregularities such as keratoconus. The patient manifested a positive adaptation to the suggested treatment and improved his visual condition.